2019
DOI: 10.1111/jcmm.14649
|View full text |Cite
|
Sign up to set email alerts
|

Novel reciprocal interaction of lncRNA HOTAIR and miR‐214‐3p contribute to the solamargine‐inhibited PDPK1 gene expression in human lung cancer

Abstract: Solamargine (SM) has been shown to have anti‐cancer properties. However, the underlying mechanism involved remains undetermined. We showed that SM inhibited the growth of non‐small cell lung cancer (NSCLC) cells, which was enhanced in cells with silencing of long non‐coding RNA (lncRNA) HOX transcript antisense RNA (HOTAIR), while it overcame by overexpression of HOTAIR. In addition, SM increased the expression of miR‐214‐3p and inhibited 3‐phosphoinositide‐dependent protein kinase‐1 (PDPK1) gene expression, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…MiR-214 has been shown to inhibit cancer cell phenotypes through interacting with lncRNAs, circRNAs or others [ 32 , 33 ]. In this study, miR-214 was confirmed to bind circEIF3K and could rescue circEIF3K-mediated CRC progression, which was in agreement with prior findings.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-214 has been shown to inhibit cancer cell phenotypes through interacting with lncRNAs, circRNAs or others [ 32 , 33 ]. In this study, miR-214 was confirmed to bind circEIF3K and could rescue circEIF3K-mediated CRC progression, which was in agreement with prior findings.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies clearly highlight the significance of miRNA-214 and HOTAIR signatures in treatment of cervical cancer. For example, the combination of miR-214 overexpression and paclitaxel treatment might be more effective in the treatment of cervical cancer than paclitaxel alone [ 32 ]. At present, some RNA-based approaches have been developed to target ncRNAs, including antisense oligonucleotides (ASOs) or siRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Many miRNAs (let-7b, let-7c, miR-21, miR-23b, miR-196b, miR-143, miR-126-3p, miR-20b-5p, miR-451a, and miR-144-3p) were identified as potential biomarkers for cervical cancer diagnosis, prognosis and cancer stage, even have been shown effective for diagnosis of cervical adenocarcinoma and high grade intraepithelial lesions [ 29 , 30 ]. MiR-214-3p was a miRNA involved in many cancer, including lung cancer, breast cancer, colon cancer, endometrial carcinoma, and pancreatic cancer in humans [ 31 , 32 ]. In cervical cancer, miR-214-3p has been found play an important roles in regulating cell proliferation, apoptosis, cell invasion, metastasis and angiogenesis [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ncRNAs have cell type, tissue and cancer specificity, thus RNA profiling has become a mean to identify useful biomarkers of tumor development, progression and metastasis. Although miRNAs represent the most widely investigated ncRNAs, lncRNAs are emerging as cancer key regulators [7,12]. Arrays and next generation sequencing (NGS) are high-throughput methods to detect and quantify ncRNAs, even though several caveats are to be considered.…”
Section: Ncrnas Expression Profilingmentioning
confidence: 99%